Fear Conditioning in Adolescents with Anxiety Disorders: Results from a Novel Experimental Paradigm - Lau, Jennifer Y. F; Lissek, Shmuel; Nelson, Eric E; Yoon, Lee; Roberson-Nay, Roxann; Poeth, Kaitlin; Jenness, Jessica; Ernst, Monique; Grillon, Christian; Pine, Daniel S (Journal of the American Academy of Child and Adolescent Psychiatry, 2008)
Considerable research examines fear conditioning in adult anxiety disorders but few studies examine youths. Adult data suggest that anxiety disorders involve elevated fear but intact differential conditioning. We used a novel paradigm to assess fear conditioning in pediatric anxiety patients. Sixteen individuals with anxiety disorders and 38 healthy comparisons viewed two photographs of actresses displaying neutral expressions. One picture served as the conditioned stimulus (CS), paired with a fearful expression and a shrieking scream (CS+), whereas the other picture served as a CS unpaired with the aversive outcome (CS-). Conditioning was indexed by self-reported fear. Subjects participated in two visits involving conditioning and extinction trials. Both groups developed greater fear of the CS+ relative to CS-. Higher fear levels collapsed across each CS characterized anxious relative to healthy subjects, but no significant interaction between group and stimulus type emerged. Fear levels at visit 1 predicted avoidance of visit 2. Fear levels to both CS types showed stability even after extinction. Consistent with adult data, pediatric anxiety involves higher fear levels following conditioning but not greater differential conditioning. Extending these methods to neuroimaging studies may elucidate neural correlates of fear conditioning. Implications for exposure therapies are discussed.